Gagasan Amandemen (Ulang) UUD 1945 (Usulan untuk Penguatan DPD dan Kekuasaan Kehakiman) - Ni'matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2008)
The urgency of the re-amendment of the Constitution of 1945 is to enhance the result of the previous amendment, which is to afford better government governance in Indonesia. Needless to say that the constitution of 1945 is sacred, as also amendment can not be taken carelessly